1986
DOI: 10.1002/ana.410200405
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic eye movement dysfunction in Alzheimer's disease

Abstract: Saccades were measured by magnetic search coil technique in 13 patients with Alzheimer's disease and compared with those of 11 age-matched control subjects. We analyzed responses to target motion of predictable and unpredictable timing or amplitude, and responses to briefly flashed targets. Latencies were significantly prolonged and peak velocities reduced only when the timing of target motion was unpredictable. Saccades to predictable amplitude targets were abnormally hypometric. In 8 patients, impersistence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
5
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(105 citation statements)
references
References 39 publications
7
92
5
1
Order By: Relevance
“…As reported previously, these abnormalities are consistent with fronto-striatal pathologies (Maruff et al, 1998;Cairney et al, 2004a, b). For example, similar patterns of impairment are observed among individuals with focal cortical lesions or neurodegenerative diseases such as Alzheimer's Disease, and Parkinson's Disease, that disrupt fronto-cortical and basal ganglia pathways (Fletcher and Sharpe, 1986;Vidailhet et al, 1994). This suggests that the same brain areas are disrupted in association with chronic petrol sniffing (Maruff et al, 1998;Cairney et al, 2004a).…”
Section: Discussionmentioning
confidence: 87%
“…As reported previously, these abnormalities are consistent with fronto-striatal pathologies (Maruff et al, 1998;Cairney et al, 2004a, b). For example, similar patterns of impairment are observed among individuals with focal cortical lesions or neurodegenerative diseases such as Alzheimer's Disease, and Parkinson's Disease, that disrupt fronto-cortical and basal ganglia pathways (Fletcher and Sharpe, 1986;Vidailhet et al, 1994). This suggests that the same brain areas are disrupted in association with chronic petrol sniffing (Maruff et al, 1998;Cairney et al, 2004a).…”
Section: Discussionmentioning
confidence: 87%
“…6 Hypometric saccades, prolonged saccade latencies, 7-11 reduced peak velocities, 8 and disorganized visual scanning 10,12 have been noted. However, an early observation suggesting that prosaccadic latencies might prove to be a reliable index of dementia severity 13 was not confirmed.…”
Section: Clinical Ocular Motor Manifestationsmentioning
confidence: 99%
“…However, an early observation suggesting that prosaccadic latencies might prove to be a reliable index of dementia severity 13 was not confirmed. 7 Furthermore, results from studies looking at the saccadic gain and velocity in AD are controversial; some studies found impairment, 8,14 whereas other studies did not. 9,15 intrusions during attempted fixation; 11 and (2) visual capture by the target in the antisaccadic paradigm, 14,[17][18][19] in which the subject has to suppress a reflexive saccade to a peripheral target and execute an endogenously driven saccade to an equal and opposite location.…”
Section: Clinical Ocular Motor Manifestationsmentioning
confidence: 99%
“…Antisaccades (i.e., volitional saccades with opposite direction to the target) in AD exhibit impaired inhibition towards the target, as well as impaired correction of errors, with the extent of the deficiencies being related to the severity of the disease (Hershey et al 1983;Fletcher and Sharpe 1986;Moser et al 1995;Shafiq-Antonacci et al 2003;Crawford et al 2005;Garbutt et al 2008). Prosaccades (i.e., saccades directed toward the target) in AD have abnormally long latencies (Hershey et al 1983;Fletcher and Sharpe 1986;Moser et al 1995;Shafiq-Antonacci et al 2003;Crawford et al 2005;Garbutt et al 2008), but see Hershey et al (1983) and Mosimann et al (2005). Saccadic gain and speed findings in AD are controversial: some studies found impairment (Fletcher and Sharpe 1986;Hotson and Steinke 1988;Shafiq-Antonacci et al 2003) whereas others did not (Moser et al 1995;Garbutt et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Prosaccades (i.e., saccades directed toward the target) in AD have abnormally long latencies (Hershey et al 1983;Fletcher and Sharpe 1986;Moser et al 1995;Shafiq-Antonacci et al 2003;Crawford et al 2005;Garbutt et al 2008), but see Hershey et al (1983) and Mosimann et al (2005). Saccadic gain and speed findings in AD are controversial: some studies found impairment (Fletcher and Sharpe 1986;Hotson and Steinke 1988;Shafiq-Antonacci et al 2003) whereas others did not (Moser et al 1995;Garbutt et al 2008). Very few studies have examined saccadic eye movements in MCI (Yang et al 2011(Yang et al , 2013, and no research has examined the characteristics of microsaccades in either AD or MCI.…”
Section: Introductionmentioning
confidence: 99%